DETERMINING THE IMPACT OF A SURGICAL LIAISON NURSE ROLE IN THE PAEDIATRIC OPERATING ROOM - MacDonald, Kathy; Latimer, Margot; Drisdelle, Nadia (Operating Room Nurses Association of Canada Journal, 2006)
A two-group (N=92) quasi-experimental pre-post test design was used to examine the effects of intra-operative communication by a surgical liaison nurse (SLN) on parental anxiety. Group I received in person progress reports from the SLN. Group II received routine perioperative care. The Speilberger’s1 State-Trait Anxiety Inventory (STAI) Scale and investigator developed family rating scales were distributed to both groups and used as a quantitative as well as a qualitative approach to determine what was helpful for the family members during the operative period. Two hundred and eighty feedback forms were dispersed to various health care professionals including all anaesthetists, surgeons, nurses and other staff in the perioperative care team, including the operating room, day surgery unit and the post anaesthetic recovery room areas. Feedback forms were also circulated to staff from the intensive care unit and the surgical in-patient units. The results showed the anxiety levels were lower for the families who received in person progress reports but the difference by group was not statistically significant. Thematic written responses provided examples of improved care and effective time management behaviours on the part of the health care professionals. Written responses provided validation for the scale scores for both families and health care professionals and were an indication of the support for the role of the surgical liaison nurse. Qualitative findings implied that the surgical liaison nurse facilitated the transfer of necessary information between the perioperative care team and the family thus providing a support mechanism for families under stress.